Pharmacognostic Study of the Involucre of Centaurea cyanus L.: Morphological, Anatomical, and Phytochemical Characteristics - Shevchenko, Yeluzaveta; Cholak, Iryna (The Ukrainian Scientific Medical Youth Journal, 2025)
one of the relevant directions for the rational use of raw material resources and reducing the cost of pharmaceuticals is the comprehensive processing of plant materials in the pharmaceutical industry. Often, during harvesting and preparation of medicinal plants, a significant amount of waste remains unused in practice, leading to the loss of valuable biologically active compounds. One such plant is the cornflower (Centaurea cyanus L.), belonging to the Asteraceae family. This plant has long been known for its medicinal properties and is widely used in both traditional and official medicine. In medicinal practice, funnel-shaped and tubular flowers of cornflower are mainly utilized due to their pronounced anti-inflammatory, diuretic, antibacterial, immunomodulatory, antioxidant, and capillary-strengthening effects, making them effective for cardiovascular disease prevention. These pharmacological properties result from the presence of a wide range of biologically active compounds, including flavonoids, hydroxycinnamic acids, tannins, and polysaccharides. However, during the harvesting of cornflower blossoms, the involucre is typically discarded, as its pharmacological potential has not been sufficiently investigated. Preliminary studies, however, indicate the promising use of this part due to its high content of biologically active substances. Thus, this study aimed to comprehensively investigate the involucre of cornflower blossoms to determine its chemical composition and evaluate its potential for use in pharmaceutical practice. To achieve this goal, microscopic and phytochemical methods of analysis according to the requirements of the State Pharmacopoeia of Ukraine (SPhU) were employed. Microscopic analysis, conducted using a scanning electron microscope (SEM, JSM-6060LA, Japan), revealed characteristic ultrastructural features, including spiral-twisted multicellular trichomes and elongated stomata located along the central vein of the involucre leaf. Additionally, distinctly visible accumulations of calcium oxalate crystals were identified on the leaf surface. Phytochemical analysis showed a high content of polyphenolic compounds (79.46±0.65 mg/g), significantly exceeding their levels in other plant parts. Additionally, water-soluble polysaccharides and pectins were identified, which are known for their anti-inflammatory, detoxifying, antibacterial, and immunostimulating properties. The obtained results suggest the cornflower involucre as a promising raw material for developing new medicinal products with pronounced therapeutic properties. Further research should focus on clarifying the full spectrum of biologically active substances, thoroughly investigating their pharmacological activities, and optimizing extraction technologies, thereby significantly contributing to the development of the domestic pharmaceutical industry.